The Effect of Escherichia coli on Pro-Inflammatory Mediators Level and Kidney and Liver Function of Sepsis in Rattus novergicus - Dian Samudra1,2, Sumarno3 , Sanarto Santoso3 , Aswoco A. Asmoro4 , Husnul Khotimah5 , Arif N. M. Ans (Indian Journal of Forensic Medicine & Toxicology, 2020)
Sepsis is a life-threatening state of organ dysfunction caused by a deregulation of the body’s response towardsan infection. The purpose of this study was to determine the pro-inflammatory mediators’ level as well askidney and liver organ function on the Rattus novergicus sepsis model injected intraperitoneally (i.p.) withE. coli. This study used 20 male rats (Rattus novergicus, Wistar strain) which were divided into 2 groups:rats without E. coli injection and rats were i.p. with 105 CFU of E. coli. After six hours, the level of proinflammatory mediators (TNF?, Hs-CRP, PCT, and MDA), kidney function (urea, BUN, and creatinine), andliver function (SGPT, SGOT, and the total of bilirubin) were examined. The data obtained were analyzed usingT-Test. This study concluded that intraperitoneal injection of E. coli increased pro-inflammatory mediatorlevels which include TNF?, Hs-CRP, PCT, MDA level. It also increased kidney function. Interestingly, theinjection only increased bilirubin total levels in the liver but did not show improvement in the SGPT andSGOT. In summary, there was a significant increase in TNF-? pro-inflammatory mediators, procalcitonin(PCT), malondialdehyde (MDA), urea kidney function parameters and BUN among treatment groups. Thehs-CRP, creatinine, and total bilirubin experienced a significant increase.